Left–right asymmetry of the gnathostome skull: Its evolutionary, developmental, and functional aspects. Issue 6 (8th May 2014) - Compagnucci, Claudia; Fish, Jennifer; Depew, Michael J.; Halpern, Marnie E.; Hobert, Oliver; Wright, Christopher V. E.
Summary Much of the gnathostome (jawed vertebrate) evolutionary radiation was dependent on the ability to sense and interpret the environment and subsequently act upon this information through utilization of a specialized mode of feeding involving the jaws. While the gnathostome skull, reflective of the vertebrate baüplan, typically is bilaterally symmetric with right (dextral) and left (sinistral) halves essentially representing mirror images along the midline, both adaptive and abnormal asymmetries have appeared. Herein we provide a basic primer on studies of the asymmetric development of the gnathostome skull, touching briefly on asymmetry as a field of study, then describing the nature of cranial development and finally underscoring evolutionary and functional aspects of left–right asymmetric cephalic development. genesis 52:515–527, 2014. © 2014 Wiley Periodicals, Inc.